2015
DOI: 10.1016/j.watres.2015.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Removal of bacterial contaminants and antibiotic resistance genes by conventional wastewater treatment processes in Saudi Arabia: Is the treated wastewater safe to reuse for agricultural irrigation?

Abstract: Please cite this article as: Al-Jassim, N., Ansari, M.I., Harb, M., Hong, P.-Y., Removal of bacterial contaminants and antibiotic resistance genes by conventional wastewater treatment processes in Saudi Arabia: Is the treated wastewater safe to reuse for agricultural irrigation?, Water Research (2015Research ( ), doi: 10.1016Research ( /j.watres.2015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(122 citation statements)
references
References 51 publications
8
110
1
3
Order By: Relevance
“…However, infectious EV was detected in the chlorinated effluent and occasionally in concentrations approximating its 50% infectious dose. These results and those of an earlier study identified antibiotic-resistant bacteria and associated resistance genes in chlorinated effluent [1], indicating a need to implement good management practices (e.g., wearing personal protective gear or clothing) when irrigating fields with treated wastewater in the local context. The presence of plant viruses in chlorinated effluent raises concerns about reuse in commercial agricultural irrigation.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, infectious EV was detected in the chlorinated effluent and occasionally in concentrations approximating its 50% infectious dose. These results and those of an earlier study identified antibiotic-resistant bacteria and associated resistance genes in chlorinated effluent [1], indicating a need to implement good management practices (e.g., wearing personal protective gear or clothing) when irrigating fields with treated wastewater in the local context. The presence of plant viruses in chlorinated effluent raises concerns about reuse in commercial agricultural irrigation.…”
Section: Discussionsupporting
confidence: 70%
“…All samples have a coliform count lower than 2.2 CFU/100 mL and meet the maximum discharge requirement for unrestricted irrigation [1,2]. The coliform counts increased in the months experiencing a lower temperature (Table S2).…”
Section: Fecal Coliform Counts In Chlorinated Effluentmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the potential for arcobacters to grow during sewage treatment, it was interesting to see that a recent study of secondary treatment WWTP in Saudi Arabia showed (by NGS) effective removal of certain genera such as Pseudomonas (4 log 10 reduction) and Arcobacter (2 log 10 reduction) from influent to effluent water (Al-Jassim et al, 2015). A further 1 log 10 removal of Arcobacter was achieved by chlorination.…”
Section: Secondary Treatmentmentioning
confidence: 99%
“…Yuan et al [21] showed that all bacteria, except erythromycin-and sulfadiazine-resistant bacteria, were inactivated fully by 15 mg Cl 2 min/L, and a chlorine dose of > 60 mg Cl 2 min/L was needed to inactivate erythromycin-and sulfadiazine-resistant bacteria. Additionally, the proportion of multidrug-resistant bacteria isolated from the chlorinated effluent increases compared to the influent, and antibiotic-resistance genes remain detectable in the chlorinated effluent [25]. Huang et al [26] also indicated that tetracycline-resistant E. coli showed a higher resistance to chlorine than tetracycline-sensitive E. coli.…”
Section: Inactivation Ratio Of Vre and Detection Of Vana In Secondarymentioning
confidence: 99%